Positive electrode material and preparation method and application thereof
By adopting the design of uniform doping element Q in the bulk phase and gradient doping element D in the shell layer in the ultra-high nickel ternary cathode material, the problems of volume change and Ni4+ degradation during the charge and discharge process of the material are solved, significantly improving the performance of the battery. Kinetic properties and cycling stability.
Patent Information
- Application Number
- CN202310868983.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-17
AI Technical Summary
The existing ultra-high nickel ternary cathode materials have significant volume changes and rapid degradation of Ni4+ surface during charging and discharging, resulting in a degradation of cycling performance and making it difficult to mass-produce in industrial use.
Through the combination of the uniform bulk doping element Q and the shell gradient doping element D, a continuous core-shell structure cathode material is designed to optimize the lithium ion transmission path and suppress the degradation of the core-shell Ni concentration difference under high-temperature baking.
The energy density, rate performance, cycle life and safety performance of the battery are significantly improved, while structural optimization and core-shell concentration difference are maintained.
Smart Images

Figure CN119324221A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used as power sources for portable electronic devices and household appliances due to their high energy density. However, when lithium-ion batteries are used as power batteries to replace internal combustion engines, even the most advanced lithium batteries currently cannot reach the range threshold of fuel vehicles, causing range anxiety for electric vehicle consumers. In addition, due to the relatively long service life of automobiles, the life of lithium-ion batteries is also required, and lithium-ion batteries are often required to be able to operate stably for more than 5 to 10 years. Ultra-high nickel ternary positive electrode material has 200mAhg -1 The above capacity and higher voltage platform are expected to significantly improve the energy density of lithium-ion batteries and alleviate the range problem of electric vehicles. However, the ultra-high nickel ternary positive electrode material has significant volume changes and surface Ni 4+ The problem of rapid degradation causes its cycle performance to decline rapidly.
[0003] At present, the existing technology uses full concentration or core-shell concentration gradient structure to solve the above problems. However, the concentration gradient control of the precursor is difficult to achieve in mass production, and the gradient will disappear during the subsequent high-temperature sintering of the precursor due to the mutual diffusion of elements. Therefore, it is still a huge challenge to produce ultra-high nickel core-shell positive electrode materials in industry.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] An object of the present invention is to provide a positive electrode material having excellent electrochemical properties by combining uniform bulk doping elements with gradient shell doping elements to achieve structural optimization and maintain core-shell concentration difference.
[0006] Another object of the present invention is to provide a method for preparing the positive electrode material, which is simple, easy to operate and environmentally friendly.
[0007] Another object of the present invention is to provide a battery.
[0008] Another object of the present invention is to provide an electrical device.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] A positive electrode material, comprising a core layer and a shell layer coated on the surface of the core layer;
[0011] The chemical formula of the core layer includes LiNix1 Co y1 Mn 1-x1-y1-z1 Q z1 O₂, 0.9 < x₁ ≤ 1, 0 ≤ y₁ < 0.05, 0 < z₁ < 0.025, x₁ + y₁ + z₁ ≤ 1, and the element Q includes at least one of Al, B, Nb, La, Sr, Sb, and Mo;
[0012] The chemical formula of the shell layer includes LiNi x2 Co y ₂Mn 1-x2-y2-z2 M z2 O₂, 0.33 < x₂ ≤ 0.9, 0 ≤ y₂ < 0.33, 0 < z₂ < 0.025, x₂ + y₂ + z₂ ≤ 1, where the element M includes the element Q and the doping element D, and the doping element D is selected from at least one of B, Sb, Nb, W, Zr, Ta, and Mo;
[0013] The element Q is uniformly distributed in the core layer and the shell layer;
[0014] The doping element D shows a radially decreasing concentration distribution from the surface to the inside of the shell layer;
[0015] The inside of the positive electrode material has a radially radial structure.
[0016] In one embodiment, the diameter of the core layer is 4 - 16 μm, and the thickness of the shell layer is 0.1 - 2 μm.
[0017] In one embodiment, the doping element D on the surface of the shell layer exists in the form of Li x DO₃, 0 < x < 2.
[0018] In one embodiment, the element Q and the element D are different elements.
[0019] In one embodiment, the distribution thickness of the element D in the positive electrode material is 0.1 - 3 μm.
[0020] In one embodiment, the crystal grain size of the 003 crystal plane of the positive electrode material is
[0021] In one embodiment, the microstrain of the positive electrode material is 0.03% - 0.09%.
[0022] A method for preparing a positive electrode material, comprising the following steps:
[0023] Roast a mixed material of a precursor material, a compound of the doping element D, and a lithium source to obtain the positive electrode material;
[0024] The precursor material has a core-shell structure, wherein the chemical formula of the core includes Ni x3 Co y3 Mn 1-x3-y3-z3 Q z1 (OH)2, 0.9 < x3 ≤ 1, 0 ≤ y3 < 0.05, 0 < z3 < 0.025, x3 + y3 + z3 ≤ 1, and the element Q is selected from at least one of Al, B, Nb, La, Sr, Sb, and Mo; the chemical formula of the shell includes Ni x4 Co y4 Mn 1-x4-y4-z4 Q z4 (OH)2, 0.33 < x4 ≤ 0.9, 0 ≤ y4 < 0.33, 0 < z4 < 0.025, x4 + y4 + z4 ≤ 1; the element Q is uniformly distributed in the core and the shell;
[0025] The doping element D is selected from at least one of B, Sb, Nb, W, Zr, Ta, and Mo.
[0026] In one embodiment, the diameter of the core is 4 - 16 μm, and the thickness of the shell is 0.1 - 2 μm.
[0027] In one embodiment, the element Q and the element D are selected from different elements.
[0028] In one embodiment, the average particle size D50 of the precursor material is 4 - 18 μm, the specific surface area is 4 - 20 m 2 / g, and the tapped density is 1.9 - 2.1 g / cm 3 .
[0029] In one embodiment, the molar ratio of the precursor material, the compound of the doping element D, and the lithium source is 1:X:(1.0 - 1.07), wherein 0 < X < 0.025.
[0030] In one embodiment, the lithium source includes at least one of LiOH, Li2CO3, Li2SO4, LiCl, and LiNO3.
[0031] In one embodiment, the preparation method of the mixed material specifically includes: performing at least one mixing treatment on the precursor material, the compound of the doping element D, and the lithium source; the rotation speed of the mixing treatment is 400 - 1500 r / min, and the time of the mixing treatment is 15 - 240 min.
[0032] In one embodiment, the calcination includes a first calcination and a second calcination performed in sequence.
[0033] In one embodiment, the first calcination temperature is 300-600° C., the heating rate is 1.5-6° C. / min, and the holding time is 3-9 h.
[0034] In one embodiment, the second calcination temperature is 600-800° C., the heating rate is 1.5-6° C. / min, and the holding time is 10-20 h.
[0035] In one embodiment, the first calcination and the second calcination are both performed under oxygen conditions; the oxygen rate is 100-400 L / min.
[0036] In one embodiment, between the first calcination and the second calcination, the process further includes: subjecting the material after the first calcination to at least one mixing treatment; the mixing treatment is performed at a rotation speed of 850 to 1200 r / min, and the mixing treatment time is 15 to 25 min.
[0037] In one embodiment, the method further includes: crushing and screening the second calcined material.
[0038] A battery comprises the positive electrode material or the positive electrode material prepared by the positive electrode material preparation method.
[0039] An electrical device comprises the battery.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] (1) The cathode material of the present invention has a continuous core-shell structure, wherein the shell layer has excellent stability and safety, and the core layer is an ultra-high nickel cathode material, providing high capacity; the doping element Q is uniformly distributed in the bulk phase of the cathode material, maintaining the radial distribution structure of the cathode material, optimizing the lithium ion transmission path, and significantly improving its kinetic performance; the doping element D is distributed in the shell layer in a concentration gradient, which can effectively inhibit the degradation of the core-shell Ni concentration difference under high-temperature calcination, and give play to the stability and safety advantages of the shell; at the same time, the radial radiation structure inside the particle can effectively dissipate micro stress and accelerate lithium ion diffusion, thereby significantly improving the energy density, rate performance, cycle life and safety performance of the battery; the present invention can simultaneously achieve structural optimization and core-shell concentration difference maintenance, thereby improving the electrochemical performance of the cathode material.
[0042] (2) The preparation method of the positive electrode material of the present invention is simple and easy, environmentally friendly, and can simultaneously achieve structural optimization of the positive electrode material and maintain the core-shell concentration difference, thereby significantly improving the electrochemical performance of the positive electrode material.
[0043] (3) The battery of the present invention has high capacity, high safety performance and high cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the description of the specific embodiments or the prior art. Obviously, the drawings in the following description are some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.
[0045] Figure 1 Scanning electron microscope image of the positive electrode material in Example 1 of the present invention;
[0046] Figure 2 Cross-sectional view and elemental analysis of the positive electrode material in Example 1 of the present invention;
[0047] Figure 3 XRD data of the positive electrode material of the present invention and its Rietveld refinement results;
[0048] Figure 4 Test cycle performance diagrams of lithium-ion batteries prepared from the positive electrode materials of Example 1, Comparative Example 1, and Comparative Example 2 of the present invention. Specific Embodiments
[0049] The following will describe the implementation schemes of the present invention in detail in combination with the embodiments. However, those skilled in the art will understand that the following embodiments are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. For those not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. Those reagents or instruments not specified by the manufacturer can all be obtained through commercial purchase as conventional products.
[0050] According to one aspect of the present invention, the present invention relates to a positive electrode material, and the positive electrode material includes a core layer and a shell layer coated on the surface of the core layer;
[0051] The chemical formula of the core layer includes LiNi x1 Co y1 Mn 1-x1-y1-z1 Q z1 O2, 0.9 < x1 ≤ 1, 0 ≤ y1 < 0.05, 0 < z1 < 0.025, x1 + y1 + z1 ≤ 1, and the element Q includes at least one of Al, B, Nb, La, Sr, Sb, and Mo;
[0052] The chemical formula of the shell layer includes LiNi x2 Co y 2Mn 1-x2-y2-z2 M z2O2, 0.33 < x2 ≤ 0.9, 0 ≤ y2 < 0.33, 0 < z2 < 0.025, x2 + y2 + z2 ≤ 1, wherein the element M includes the element Q and a doping element D, and the doping element D is selected from at least one of B, Sb, Nb, W, Zr, Ta, and Mo;
[0053] The element Q is uniformly distributed in the core layer and the shell layer;
[0054] The doping element D shows a decreasing radial concentration distribution from the surface to the interior of the shell layer;
[0055] The interior of the positive electrode material has a radial structure.
[0056] The positive electrode material of the present invention has a continuous core - shell structure. Among them, the shell layer has excellent stability and safety, the core layer is a high - nickel positive electrode material that provides high capacity; the doping element Q is uniformly distributed in the bulk phase of the positive electrode material, maintaining the radial distribution structure of the positive electrode material, thereby optimizing the lithium - ion transmission path and significantly improving its kinetic performance. At the same time, the radial distribution structure can effectively dissipate stress, effectively alleviate the particle cracking caused by the volume change of high - nickel or ultra - high - nickel materials, and effectively improve the cycle performance; the doping element D shows a concentration gradient distribution in the shell layer, which can effectively inhibit the degradation of the Ni concentration difference between the core and the shell under high - temperature calcination, and give play to the advantages of the stability and safety of the shell. Through the overall uniform doping of the doping element Q and the concentration - gradient distribution doping of the doping element D in the shell layer, the two cooperate to simultaneously achieve structure optimization and maintenance of the core - shell concentration difference, and improve the electrochemical performance of the positive electrode material.
[0057] In one embodiment, the value of x1 includes but is not limited to 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, or 1; the value of y1 includes but is not limited to 0.01, 0.02, 0.03, 0.04, or 0.05; the value of z1 includes but is not limited to 0.01, 0.015, 0.018, 0.02, 0.021, 0.022, 0.023, 0.024, or 0.025; the value of x1 + y1 + z1 includes but is not limited to 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, or 0.99.
[0058] In one embodiment, the value of x2 includes but is not limited to 0.34, 0.35, 0.038, 0.4, 0.5, 0.6, 0.7, 0.8, or 0.9; the value of y2 includes but is not limited to 0.01, 0.05, 0.08, 0.1, 0.15, 0.18, 0.2, 0.25, 0.28, 0.3, or 0.33; the value of z2 includes but is not limited to 0.01, 0.015, 0.018, 0.02, 0.021, 0.022, 0.023, 0.024, or 0.025; the value of x2 + y2 + z2 includes but is not limited to 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.08, or 0.99.
[0059] In one embodiment, the element Q and the element D are different elements.
[0060] In one embodiment, the distribution thickness of the element D in the positive electrode material is 0.1 - 3 μm, such as 0.1 μm, 0.15 μm, 0.18 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.2 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, etc. In one embodiment, the particle shape of the positive electrode material of the present invention is spherical or quasi-spherical. The distribution thickness L of the element D in the positive electrode material of the present invention is L = L2 - L1, where L1 represents the distance between the element D closest to the center of the sphere of the positive electrode material and the center of the sphere, and L2 represents the distance between the element D farthest from the center of the sphere of the positive electrode material and the center of the sphere.
[0061] In one embodiment, the diameter of the core layer is 4 - 16 μm, such as 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, etc.; the thickness of the shell layer is 0.1 - 2 μm, such as 0.1 μm, 0.2 μm, 0.5 μm, 0.7 μm, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, or 2 μm, etc. The positive electrode material of the present invention has a core layer with a suitable diameter and a shell layer with a suitable thickness, and the combination of the two is more conducive to ensuring the electrochemical performance of the positive electrode material.
[0062] In one embodiment, the doping element D on the surface of the shell layer is in the form of Li x DO3, where 0 < x < 2, such as 0.1, 1, 1.5, etc.
[0063] In one embodiment, the grain size of the 003 crystal plane of the positive electrode material is For example etc.
[0064] In one embodiment, the microstrain of the positive electrode material is 0.03% to 0.09%, such as 0.03%, 0.034%, 0.035%, 0.038%, 0.04%, 0.045%, 0.048%, 0.05%, 0.055%, 0.06%, 0.07%, 0.08%, 0.09%, etc.
[0065] The positive electrode material of the present invention has a low grain size and a high microstrain, indicating that the bulk-phase uniformly doped element Q refines the grains, and the shell-doped element D is beneficial to maintaining the core-shell structure. Among them, both the microstrain and the grain size can be obtained by XRD analysis. The grain size is a scale representing the grain size and can be calculated by the Scherrer formula. The microstrain is caused by the inhomogeneous plastic flow generated when the plastic material undergoes deformation and phase transformation, resulting in micro-region (tens of angstroms) strain inside the material. This strain can also be caused by the anisotropic shrinkage of grains with different orientations in a multiphase material, the inconsistent shrinkage of adjacent phases, or coherent distortion, and can be calculated by the William-Hall method.
[0066] According to another aspect of the present invention, the present invention also relates to a method for preparing a positive electrode material, comprising the following steps:
[0067] Roasting a mixed material of a precursor material, a compound of a doping element D, and a lithium source to obtain a positive electrode material;
[0068] The precursor material has a core-shell structure, wherein the chemical formula of the inner core includes Ni x3 Co y3 Mn 1-x3-y3-z3 Q z1 (OH)2, 0.9 < x3 ≤ 1, 0 ≤ y3 < 0.05, 0 < z3 < 0.025, x3 + y3 + z3 ≤ 1, and the element Q is selected from at least one of Al, B, Nb, La, Sr, Sb, and Mo; the chemical formula of the outer shell includes Ni x4 Co y4 Mn 1-x4-y4-z4 Q z4 (OH)2, 0.33 < x4 ≤ 0.9, 0 ≤ y4 < 0.33, 0 < z4 < 0.025, x4 + y4 + z4 ≤ 1; the element Q is uniformly distributed in the inner core and the outer shell;
[0069] The doping element D is selected from at least one of B, Sb, Nb, W, Zr, Ta, and Mo.
[0070] The method for preparing the positive electrode material of the present invention is simple and easy to implement, environmentally friendly, can simultaneously optimize the structure of the positive electrode material and maintain the core-shell concentration difference, and significantly improve the electrochemical performance of the positive electrode material.
[0071] In one embodiment, the element Q and the element D are selected from different elements.
[0072] In one embodiment, the diameter of the core is 4 to 16 μm, such as 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, etc. The thickness of the shell is 0.1 to 2 μm, such as 0.1 μm, 0.2 μm, 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm, etc. The precursor material of the present invention has a suitable core diameter and shell thickness, thereby ensuring the coordination of the core-shell material, which is beneficial to the electrochemical performance of the obtained positive electrode material.
[0073] In one embodiment, the average particle size D50 of the precursor material is 4 to 18 μm, such as 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, etc. The specific surface area of the precursor material is 4 to 20 m 2 / g, for example, 4m 2 / g, 5m 2 / g, 6m 2 / g, 8m 2 / g, 10m 2 / g, 12m 2 / g, 15m 2 / g, 18m 2 / g, 20m 2 The tap density of the precursor material is 1.9 to 2.1 g / cm 3 , for example 1.9 g / cm 3 , 1.95g / cm 3 , 2g / cm 3 , 2.05g / cm 3 , 2.1g / cm 3 The precursor material of the present invention has a suitable average particle size D50, specific surface area and tap density, thereby laying a good foundation for preparing a positive electrode material with excellent electrochemical performance.
[0074] In one embodiment, the precursor material originates from Huayou Cobalt.
[0075] In one embodiment, the synthesis of the precursor material refers to the reference: Adv. Energy Mater. 2023, 13, 2204291. In one embodiment, the precursor material is prepared by a co-precipitation technique, including the following steps: Dissolve NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O in deionized water in stoichiometric proportions. As the particle size increases, control the transition metal composition by changing the Ni∶Co∶Mn molar ratio from 1:0:0 to 0.65:0.21:0.14. Continuously pump the prepared aqueous metal sulfate solution into a batch reactor at a rate of 500 mL h -1 and simultaneously pump ammonia water (molar ratio: NH4OH / transition metal = 1.0) and NaOH solution into the reactor to control the pH level. The reaction time is 25 h, the pH is maintained at 11.1, and the reactor temperature is maintained at 45 °C. After washing and drying, the precursor material is obtained.
[0076] In one embodiment, the molar ratio of the precursor material, the compound of doping element D, and the lithium source is 1:X:(1.0 - 1.07), where 0 < X < 0.025, such as 0.01, 0.012, 0.015, 0.018, 0.02, 0.021, 0.022, 0.023, 0.024, etc.
[0077] In one embodiment, the lithium source includes at least one of LiOH, Li2CO3, Li2SO4, LiCl, and LiNO3.
[0078] In one embodiment, the compound of doping element D includes the oxide of doping element D, such as at least one of Nb2O5, WO3, Sb2O3, Ta2O5, and MoO3.
[0079] In one embodiment, the preparation method of the mixed material specifically includes: performing at least one mixing treatment on the precursor material, the compound of doping element D, and the lithium source; the rotation speed of the mixing treatment is 400 - 1500 r / min, such as 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min, 1000 r / min, 1200 r / min, 1300 r / min, 1400 r / min, 1500 r / min, etc.; the time of the mixing treatment is 15 - 240 min, such as 15 min, 20 min, 60 min, 120 min, 240 min, etc. In one embodiment, the ball-to-material ratio of the mixing treatment is (4 - 6):1. The present invention adopts an appropriate mixing rotation speed and mixing time to fully mix the materials and form a uniform mixture.
[0080] In one embodiment, the calcination includes a first calcination and a second calcination performed sequentially.
[0081] In one embodiment, the temperature of the first calcination is 300-600°C, for example, 300°C, 350°C, 400°C, 500°C, 600°C, etc.; the heating rate is 1.5-6°C / min, for example, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min; the holding time is 3-9h, for example, 3h, 4h, 5h, 6h, 7h, 8h, 9h, etc.
[0082] In one embodiment, the temperature of the second calcination is 600-800°C, for example, 600°C, 650°C, 700°C, 750°C, 800°C, etc.; the heating rate is 1.5-6°C / min, for example, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min; the holding time is 10-20h, for example, 10h, 12h, 13h, 15, 16h, 17h, 20h, etc.
[0083] The present invention adopts two calcination treatments, uses appropriate calcination temperature, heating rate and holding time, so that the positive electrode material obtains a specific microstructure, ensures that the concentration of the D doping element is distributed in a gradient decreasing manner from the outside to the inside of the shell, which is beneficial to ensuring the cycle performance and stable performance of the positive electrode material.
[0084] In one embodiment, the first calcination and the second calcination are both carried out under oxygen conditions; the oxygen rate is 100-400 L / min, for example, 100 L / min, 150 L / min, 200 L / min, 250 L / min, 300 L / min, 400 L / min, etc.
[0085] In one embodiment, between the first calcination and the second calcination, it also includes: mixing the material after the first calcination at least once. The present invention uses the first calcination treatment to preliminarily remove hydrogen elements so that the material has a specific microstructure; the material obtained by the first calcination treatment is mixed, and the rotation speed of the mixing treatment is 850-1200r / min, such as 850r / min, 860r / min, 870r / min, 900r / min, 920r / min, 930r / min, 950r / min, 1100r / min, etc. The mixing time is 15-25min, such as 15min, 8min, 20min, 25min, etc., through suitable mixing conditions, and then ensure the specific distribution of doping elements and the particle size of the positive electrode material; It is beneficial to the later second calcination treatment to obtain a positive electrode material with excellent electrochemical properties. In one embodiment, the ball-to-material ratio of the mixing treatment is (4-6):1.
[0086] In one embodiment, the method further includes: crushing and screening the second calcined material.
[0087] According to another aspect of the present invention, the present invention also relates to a battery, comprising the positive electrode material as described above or the positive electrode material prepared by the method for preparing the positive electrode material as described above.
[0088] The battery of the present invention has high capacity, high stability and excellent cycle performance.
[0089] According to another aspect of the present invention, the present invention also relates to an electrical device, comprising the battery as described above.
[0090] The following is further explained in conjunction with specific embodiments and comparative examples.
[0091] Example 1
[0092] A method for preparing an ultra-high nickel core-shell positive electrode material comprises the following steps:
[0093] (1) Obtaining a spherical core-shell precursor Ni with an overall molar ratio of Ni:Co:Mn:Al = 94:3:2:1 0.94 Co 0.03 Mn 0.02 Al 0.01 (OH)2, D50 is 12μm, its inner core radius is 5.6μm, in terms of molar ratio, Ni:Co:Mn:Al in the inner core is 97.45:1.39:0.16:1, its shell thickness is 0.4μm, and Ni:Co:Mn:Al in the outer shell is 79:10:10:1, wherein the bulk phase uniformly doped element is Al, and the doping molar amount is 1%;
[0094] (2) According to LiOH:MoO3:Ni 0.94 Co 0.03 Mn 0.02 Al 0.01 The ingredients were prepared in a molar ratio of (OH)2=1.02:0.005:1, and mixed evenly by a high-speed mixer at a speed of 900 r / min for 20 min, and mixed twice to obtain a mixture after sufficient mixing;
[0095] (3) The mixture was first calcined at 500°C for 4 hours, and after the reaction, it was taken out and mixed again in a high-speed mixer at a speed of 900 r / min and a mixing time of 20 min. After mixing once, it was fully mixed and then calcined at 760°C for 10 hours. The calcination heating rate was 3.0°C / min. The calcination atmosphere was oxygen and the air intake rate was 200 L / min.
[0096] (4) The calcined product is crushed and sieved to obtain the ultra-high nickel core-shell positive electrode material LiNi 0.935 Co 0.03 Mn 0.02 Al 0.01 Mo 0.005 O2, in which the doping element Al is evenly distributed in the bulk phase, and Mo is mainly distributed in the outer shell.
[0097] Example 2
[0098] A method for preparing an ultra-high nickel core-shell positive electrode material comprises the following steps:
[0099] (1) Obtaining a spherical core-shell precursor Ni with an overall ratio of Ni:Co:Mn:B = 92:4:3:1 0.92 Co 0.04 Mn 0.03 B 0.01 (OH)2, D50 is 14μm, its core radius is 6.5μm, the molar ratio is Ni:Co:Mn:B=95.24:2.5:1.26:1, its shell thickness is 0.5μm, the molar ratio is Ni:Co:Mn:B=79:10:10:1; the bulk phase uniformly doped element is B, and the doping molar amount is 1%;
[0100] (2) According to LiOH:Ta2O5:Ni 0.92 Co 0.04 Mn 0.03 B 0.01 The ingredients were prepared in a molar ratio of (OH)2=1.03:0.0025:1, and mixed evenly by a planetary ball mill. The ball milling time was set to 1h, the rotation speed was 400r / min, the ball-to-material ratio was 6:1, and a mixture was obtained after sufficient mixing;
[0101] (3) The mixture was first calcined at 550°C for 6 hours, and after the reaction, it was taken out and mixed again in a high-speed mixer at a speed of 950 r / min and a mixing time of 15 min. After mixing once, the mixture was heated to 780°C and kept at this temperature for 12 hours. The heating rate of the calcination was 2.5°C / min, the atmosphere was oxygen, and the air intake rate was 250 L / min.
[0102] (4) The calcined product is crushed and sieved to obtain the ultra-high nickel core-shell positive electrode material LiNi 0.915 Co 0.04 Mn 0.03 B 0.01 Ta 0.005 O2, in which the doping element B is evenly distributed in the bulk phase, and Ta is mainly distributed on the surface layer or grain boundary of the shell primary particles.
[0103] Example 3
[0104] A method for preparing an ultra-high nickel core-shell positive electrode material comprises the following steps:
[0105] (1) Obtaining a spherical core-shell precursor Ni with an overall ratio of Ni:Co:Mn:Nb = 90:5:4:1 0.90 Co 0.05 Mn 0.04 Nb 0.01 (OH)2, D50 is 10μm, its core radius is 4.5μm, the molar ratio is Ni:Co:Mn:B=95.24:2.5:1.26:1, its shell thickness is 0.5μm, the molar ratio is Ni:Co:Mn:B=75:15:9:1; the bulk phase uniformly doped element is B, and the doping molar amount is 1%;
[0106] (2) According to LiOH:Sb2O3:Ni 0.90 Co 0.05 Mn 0.04 Nb 0.01 The ingredients were prepared in a molar ratio of (OH)2=1.03:0.0025:1, and mixed evenly by a planetary ball mill. The ball milling time was set to 2h, the rotation speed was 500r / min, the ball-to-material ratio was 6:1, and a mixed material was obtained after sufficient mixing;
[0107] (3) The mixture was first calcined at 500°C for 6 hours, and after the reaction, it was taken out and mixed again in a high-speed mixer at a speed of 1100 r / min and a mixing time of 20 minutes. After mixing once, the mixture was fully mixed and then heated to 790°C for 15 hours. The heating rate of the calcination was 3°C / min, the atmosphere was oxygen, and the air intake rate was 250 L / min.
[0108] (4) The calcined product is crushed and sieved to obtain the ultra-high nickel core-shell positive electrode material LiNi 0.895 Co 0.05 Mn 0.04 Nb 0.01 Sb 0.005 O2, in which the doping element Nb is evenly distributed in the bulk phase, and Sb shows a radial distribution along the grain boundaries of the primary particles, with the concentration decreasing from the outside to the inside.
[0109] Example 4
[0110] A method for preparing an ultra-high nickel core-shell positive electrode material comprises the following steps:
[0111] (1) Obtaining a spherical core-shell precursor Ni with an overall ratio of Ni:Co:Mn:Al:La=90:5:4:0.75:0.25 0.90 Co 0.05 Mn 0.04 Al 0.0075 La 0.0025 (OH)2, D50 is 12μm, its inner core radius is 5μm, the molar ratio is Ni:Co:Mn:Al:La=95.82:2.82:0.36:0.75:0.25, its shell thickness is 1μm, the molar ratio is Ni:Co:Mn:Al:La=82:8:9:0.75:0.25; the bulk phase is uniformly doped with Al and La, and the doping molar amounts are 0.75% and 0.25% respectively;
[0112] (2) According to LiOH:WO3:Ni 0.90 Co 0.05 Mn 0.04 Al 0.0075 La 0.0025 The ingredients were prepared in a molar ratio of (OH)2=1.03:0.005:1, and mixed evenly by a planetary ball mill. The ball milling time was set to 4h, the rotation speed was 500r / min, the ball-to-material ratio was 6:1, and a mixture was obtained after sufficient mixing;
[0113] (3) The mixture was first calcined at 500°C for 6 hours, and after the reaction, it was taken out and mixed again in a high-speed mixer at a speed of 1100 r / min and a mixing time of 20 min. After mixing once, the mixture was fully mixed and then heated to 800°C for 12 hours. The heating rate of the calcination was 3°C / min, the atmosphere was oxygen, and the air intake rate was 250 L / min.
[0114] (4) The calcined product is crushed and sieved to obtain the ultra-high nickel core-shell positive electrode material LiNi 0.895 Co 0.05 Mn 0.04 Al0.0075 La 0.0025 W 0.005 O2, in which the doping elements Al and La are evenly distributed in the bulk phase, W is doped in the shallow surface layer of the particles, and the W that does not enter the bulk phase is doped with Li x The primary particles are coated in the form of WO3, showing the characteristics of radial distribution as a whole, with the concentration decreasing from the outside to the inside.
[0115] Example 5
[0116] A method for preparing an ultra-high nickel core-shell positive electrode material comprises the following steps:
[0117] (1) Obtaining a spherical core-shell precursor Ni with an overall ratio of Ni:Co:Mn:Al = 95:2:2:1 0.95 Co 0.02 Mn 0.02 Al 0.01 (OH)2, D50 is 16μm, its core radius is 7μm, the molar ratio is Ni:Co:Mn:Al=98.45:0.52:0.03:1, its shell thickness is 1μm, the molar ratio is Ni:Co:Mn:Al=82:8:9:1. The bulk phase uniformly doped element is Al, and the doping molar amount is 1%;
[0118] (2) According to LiOH:Nb2O5:ZrO2:Ni 0.95 Co 0.02 Mn 0.02 Al 0.01 The ingredients were prepared in a molar ratio of (OH)2=1.02:0.0025:0.005:1, and mixed evenly by a high-speed mixer at a rotation speed of 1500 r / min and a mixing time of 20 min. The mixture was mixed twice to obtain a mixture after being fully mixed;
[0119] (3) The mixture was first calcined at 450°C for 5 hours, and after the reaction, it was taken out and mixed again in a high-speed mixer at a speed of 1100 r / min and a mixing time of 20 min. After mixing once, the mixture was fully mixed and then heated to 740°C for 15 hours. The heating rate of the calcination was 3°C / min, the atmosphere was oxygen, and the air intake rate was 250 L / min.
[0120] (4) The calcined product is crushed and sieved to obtain the ultra-high nickel core-shell positive electrode material LiNi 0.94 Co 0.02 Mn 0.0 2Al 0.01 Nb 0.005 Zr 0.005O2, in which the doping element Al is evenly distributed in the bulk phase, Sb and Zr show radial distribution characteristics along the grain boundaries of the primary particles, and form doping in the shallow surface layer of the particles, and the concentration decreases from the outside to the inside.
[0121] Comparative Example 1
[0122] A method for preparing an undoped ultra-high nickel core-shell positive electrode material, the specific process is as follows:
[0123] (1) Obtaining a spherical core-shell precursor Ni with an overall ratio of Ni:Co:Mn=93:4:3 0.93 Co 0.04 Mn 0.03 (OH)2, D50 is 14 μm, its inner core radius is 6.5 μm, the molar ratio is Ni:Co:Mn=96.24:2.5:1.26, its shell thickness is 0.5 μm, and the molar ratio is Ni:Co:Mn=80:10:10;
[0124] (2) According to LiOH:Ni 0.93 Co 0.04 Mn 0.03 The ingredients were prepared in a molar ratio of (OH)2=1.03:1, and mixed evenly by a high-speed mixer at a rotation speed of 1000 r / min and a mixing time of 20 min. The mixture was mixed twice to obtain a mixture after being fully mixed;
[0125] (3) The mixture was first calcined at 500°C for 4 hours, and after the reaction, it was taken out and mixed again in a high-speed mixer at a speed of 900 r / min and a mixing time of 20 min. After mixing once, it was fully mixed and then calcined at 760°C for 10 hours. The calcination heating rate was 3.0°C / min. The calcination atmosphere was oxygen and the air intake rate was 200 L / min.
[0126] (4) The calcined product is crushed and sieved to obtain the ultra-high nickel core-shell positive electrode material LiNi 0.93 Co 0.04 Mn 0.03 O2.
[0127] Comparative Example 2
[0128] A method for preparing a conventional ultra-high nickel positive electrode material, the specific process is as follows:
[0129] (1) Obtaining a spherical precursor Ni with an overall ratio of Ni:Co:Mn = 93:4:3 0.93 Co 0.04 Mn 0.03 (OH)2, D50 is 14 μm;
[0130] (2) According to LiOH:Ni 0.93Co 0.04 Mn 0.03 The ingredients were prepared in a molar ratio of (OH)2=1.03:1, and mixed evenly by a high-speed mixer at a rotation speed of 1500 r / min and a mixing time of 20 min. The mixture was mixed twice to obtain a mixture after being fully mixed;
[0131] (3) The mixture was first calcined at 500°C for 4 hours, and after the reaction, it was taken out and mixed again in a high-speed mixer at a speed of 900 r / min and a mixing time of 20 min. After mixing once, it was fully mixed and then calcined at 760°C for 10 hours. The calcination heating rate was 3.0°C / min. The calcination atmosphere was oxygen and the air intake rate was 200 L / min.
[0132] (4) The calcined product is crushed and sieved to obtain the ultra-high nickel positive electrode material Li Ni 0.93 Co 0.04 Mn 0.03 O2.
[0133] Comparative Example 3
[0134] A method for preparing a selectively doped ultra-high nickel positive electrode material, the specific process is as follows:
[0135] (1) Obtaining a spherical precursor Ni with an overall ratio of Ni:Co:Mn:Al = 92:4:3:1 0.92 Co 0.04 Mn 0.03 Al 0.01 (OH)2, D50 is 14μm; the bulk phase uniformly doped element is Al, and the doping molar amount is 1%;
[0136] (2) According to LiOH:Ta2O5:Ni 0.92 Co 0.04 Mn 0.03 Al 0.01 The ingredients were prepared in a molar ratio of (OH)2=1.03:0.0025:1, and mixed evenly by a planetary ball mill. The ball milling time was set to 20 min, the rotation speed was 900 r / min, and a mixture was obtained after sufficient mixing;
[0137] (3) calcining the mixture at 500°C for 4 hours and then at 760°C for 10 hours, with a heating rate of 3.0°C / min; the calcination atmosphere was oxygen, and the air intake rate was 200L / min;
[0138] (4) The calcined product is crushed and sieved to obtain the ultra-high nickel core-shell positive electrode material LiNi 0.915 Co 0.04 Mn 0.03 Al 0.01 Ta0.005 O2, in which the doping element Al is evenly distributed in the bulk phase, and Ta is mainly distributed on the surface layer or grain boundary of the shell primary particles.
[0139] Experimental example
[0140] 1. The cross-section of the positive electrode material in Example 1 was characterized by scanning electron microscopy. Figure 1 As shown, the interior of the particles has a radially distributed dense structure, and the primary particles grow evenly and are relatively narrow and long.
[0141] Second, the cross section of the positive electrode material in Example 1 was subjected to elemental analysis by electron probe microanalysis technology, such as Figure 2 As shown, the elemental composition of the core and shell of the particles has obvious differences. The molar ratio of each element at the core layer 001 position is: Ni:Co:Mn:Al:Mo=95.2:2.2:1.4:1.1:0.1, and the molar ratio of each element at the shell layer 002 position is: Ni:Co:Mn:Al:Mo=82.2:6.8:9.4:0.9:0.7. It can be seen that the nickel content of the core is significantly higher than that of the shell, the Al element is evenly distributed in the particles, and the Mo content is more in the shell than in the core.
[0142] 3. XRD data of the ultra-high nickel core-shell cathode material prepared in Example 1 and its Rietveld refinement results are shown in Figure 3 As shown in Table 1, the prepared ultra-high nickel core-shell cathode material still has a hexagonal layered structure and good crystallinity. Through further analysis based on the Scherrer formula and the William-Hall formula in the refinement software Topas, the grain size D003 and micro stress of the 003 crystal plane of the material can also be obtained. See Table 1 for details.
[0143] Table 1 Grain size and micro stress of positive electrode materials
[0144] Group D003(Angstrom) Micro strain (%) Example 1 897 0.045 Example 2 1216 0.039 Example 3 1250 0.034 Example 4 856 0.055 Example 5 763 0.049 Comparative Example 1 1680 0.025 Comparative Example 2 1896 0.011 Comparative Example 3 1325 0.023
[0145] In the positive electrode material, the smaller the grain size of the 003 crystal plane, the more slender the primary particles are, and the radial arrangement structure (i.e., the primary particles point from the center of the sphere to the sphere) is more significant; microscopic strain is related to the change of lattice constant. When there is a core-shell structure, the lattice parameters of the core and the shell are different, so there will be microscopic strain between the core and the shell. This strain is reflected as peak broadening in the XRD spectrum. The larger the microscopic strain, the greater the difference in the lattice parameters between the core and the shell, and the more significant the core-shell structure. As shown in Table 1, compared with Comparative Examples 1 to 3, the ultra-high nickel core-shell positive electrode materials prepared in Examples 1 to 5 have lower grain size of the 003 surface and higher microscopic strain, indicating that the bulk uniformly doped elements refine the particles, and the shell doping elements are conducive to the maintenance of the core-shell structure. Comparative Example 1 has a higher grain size of the 003 crystal plane due to the lack of Q and D doping, indicating that its radial structure is poor; it has a lower microscopic strain value, indicating that its core-shell gradient decreases significantly.
[0146] 3. Battery electrochemical performance test
[0147] The positive electrode materials of the embodiment and the comparative example were respectively prepared into button-type lithium-ion batteries, and performance tests were performed. The preparation methods of the button-type lithium-ion batteries corresponding to the positive electrode materials of the embodiment and the comparative example respectively comprise the following steps:
[0148] The positive electrode material powder was mixed with acetylene black and polyvinylidene fluoride (mass ratio was 90:6:4), and an appropriate amount of N-methylpyrrolidone was added as a dispersant, and the mixture was ground into a slurry. The slurry was then evenly coated on an aluminum foil, and after vacuum drying at 120°C for 10 hours, the dried electrode was rolled with a roller machine, and the aluminum foil was cut with a slicer into a circular electrode with a diameter of 1.3 cm. The loading amount of the positive electrode material on the circular electrode was controlled to be 10 mg / cm 2 . The half-cell was assembled in an argon atmosphere glove box, where the water partial pressure was ≤0.1ppm and the oxygen partial pressure was ≤0.1ppm. Metallic lithium was used as the counter electrode and 1MLiPF6 (FEC / EC / DMC, volume ratio 1:1:1) solution was used as the electrolyte. The assembled specification was a CR2032 type button lithium-ion secondary battery. Then, the constant current charge and discharge mode was used, and the capacity test was 0.1C charge and 0.1C discharge, 2.8~4.3V, vs.Li + / Li; Cycle test: 1C charge and 1C discharge at 45°C, 2.7~4.25V vs.Li + / Li, the number of cycles is 100.
[0149] The test results are shown in Table 2. The test cycle performance of the lithium ion battery obtained by using the ultra-high nickel positive electrode materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 is shown in Table 2. Figure 4 shown.
[0150] Table 2 Test results
[0151]
[0152]
[0153] As can be seen from Table 2, in the electrochemical test of lithium-ion batteries, excellent charge and discharge specific capacity and cycle stability are shown. This is because the selective doping maintains the radial distribution structure of the positive electrode material, retains the nickel, cobalt and manganese concentration difference of the core-shell, improves the kinetic properties of lithium ions, and combines the high capacity of high-nickel materials with high stability.
[0154] Compared with Comparative Example 1, although both have a core-shell structure, Example 1 can better retain and optimize the core-shell structure, improve capacity, and significantly improve cycle performance through selective doping or shell coating. Compared with Comparative Example 2, Example 1 has a specific core-shell structure, which avoids direct exposure of high-nickel materials in the electrolyte, effectively stabilizes the surface of the particles, and significantly improves the cycle performance of the material. Compared with Comparative Example 3, although both use a selective doping method, since Comparative Example 3 does not have a specific core-shell structure, its capacity and cycle performance are also reduced compared with Example 1.
[0155] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A positive electrode material, characterized in that: The positive electrode material comprises a core layer and a shell layer coated on the surface of the core layer; The chemical formula of the core layer includes LiNi x1 Co y1 Mn 1-x1-y1-z1 Q z1 O2, where 0.9 < x1 ≤ 1, 0 ≤ y1 < 0.05, 0 < z1 < 0.025, and x1 + y1 + z1 ≤ 1, and the element Q includes at least one of Al, B, Nb, La, Sr, Sb, and Mo; The chemical formula of the shell layer includes LiNi x2 Co y2 Mn 1-x2-y2-z2 M z2 O2, where 0.33 < x2 ≤ 0.9, 0 ≤ y2 < 0.33, 0 < z2 < 0.025, and x2 + y2 + z2 ≤ 1. Here, the element M includes the element Q and the doping element D, and the doping element D is selected from at least one of B, Sb, Nb, W, Zr, Ta, and Mo; The element Q is evenly distributed in the core layer and the shell layer; The doping element D is distributed in a radially decreasing concentration from the surface to the inside of the shell layer; The interior of the positive electrode material is in a radially radiating structure.
2. The positive electrode material according to claim 1, characterized in that The diameter of the core layer is 4-16 μm, and the thickness of the shell layer is 0.1-2 μm.
3. The positive electrode material according to claim 1, characterized in that Contains at least one of the following features (1) to (3): (1) The doping element D on the surface of the shell layer is Li x DO3 exists in the form of 0 <x<2; (2) The element Q and the element D are different elements; (3) The element D is distributed in the positive electrode material in a thickness of 0.1 to 3 μm.
4. The positive electrode material according to claim 1, characterized in that Contains at least one of the following features (1) to (2): (1) The grain size of the 003 crystal plane of the positive electrode material is (2) The microscopic strain of the positive electrode material is 0.03% to 0.09%.
5. A method for preparing a positive electrode material, characterized in that: The following steps are involved: The precursor material, the compound doped with the element D and the lithium source are mixed and calcined to obtain a positive electrode material; The precursor material has a core-shell structure, wherein the chemical formula of the core includes Ni x3 Co y3 Mn 1-x3-y3-z3 Q z1 (OH)2, 0.9 < x3 ≤ 1, 0 ≤ y3 < 0.05, 0 < z3 < 0.025, x3 + y3 + z3 ≤ 1, and the element Q is selected from at least one of Al, B, Nb, La, Sr, Sb, and Mo; the chemical formula of the shell includes Ni x4 Co y4 Mn 1-x4-y4-z4 Q z4 (OH)2, 0.33 < x4 ≤ 0.9, 0 ≤ y4 < 0.33, 0 < z4 < 0.025, x4 + y4 + z4 ≤ 1; the element Q is uniformly distributed in the core and the shell; The doping element D is selected from at least one of B, Sb, Nb, W, Zr, Ta and Mo.
6. The method for preparing the positive electrode material according to claim 5, characterized in that: Contains at least one of the following features (1) to (5): (1) The diameter of the inner core is 4 to 16 μm, and the thickness of the outer shell is 0.1 to 2 μm; (2) The average particle size D50 of the precursor material is 4 to 18 μm, and the specific surface area is 4 to 20 m 2 / g, tap density is 1.9~2.1g / cm 3 ; (3) The molar ratio of the precursor material, the compound of the doping element D and the lithium source is 1:X:(1.0-1.07), wherein 0 <X<0.025; (4) The lithium source includes at least one of LiOH, Li2CO3, Li2SO4, LiCl and LiNO3; (5) The doping element D and the element Q are selected from different elements.
7. The method for preparing the positive electrode material according to claim 5, characterized in that: The method for preparing the mixed material specifically comprises: mixing the precursor material, the compound of the doping element D and the lithium source at least once; the rotation speed of the mixing process is 400 to 1500 r / min, and the time of the mixing process is 15 to 240 min.
8. The method for preparing the positive electrode material according to claim 5, characterized in that: The invention comprises at least one of the following features (1) to (6): (1) The roasting includes a first roasting and a second roasting performed sequentially; (2) The temperature of the first calcination is 300-600° C., the heating rate is 1.5-6° C. / min, and the holding time is 3-9 h; (3) The temperature of the second calcination is 600-800° C., the heating rate is 1.5-6° C. / min, and the holding time is 10-20 h; (4) The first calcination and the second calcination are both carried out under oxygen conditions; the oxygen rate is 100 to 400 L / min; (5) Between the first calcination and the second calcination, the process further includes: subjecting the material after the first calcination to at least one mixing process; the mixing process is performed at a speed of 850 to 1200 r / min and for a time of 15 to 25 min; (6) The method further includes: crushing and screening the second calcined material.
9. A battery, characterized in that: The invention comprises the positive electrode material according to any one of claims 1 to 4 or the positive electrode material prepared by the method for preparing the positive electrode material according to any one of claims 5 to 8.
10. An electrical device, characterized in that: A battery comprising the battery of claim 9.
Citation Information
Cited By
Ultrahigh nickel layered oxide positive electrode material and application thereof
CN120089737A
Modified high-nickel positive electrode material and preparation method thereof
CN120527366A
Metal hydroxide precursor particle and preparation method and application thereof
CN121672605A